2017
DOI: 10.1155/2017/9164156
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Floor Augmentation Using an Equine-Derived Graft Material: Preliminary Results in 17 Patients

Abstract: Objective Sinus floor elevation with lateral approach is probably the most frequently performed reconstructive procedure to rehabilitate posterior maxilla when a bone deficiency is present. Different graft materials have been proposed and tested, often with high clinical performances and predictable results. Histological analysis is required when evaluating new materials. We investigated human biopsies retrieved after sinus floor elevation procedure by histomorphometric evaluation to test the performance of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The histomorphometric analyses revealed a mean formation of the new bone of 23.5% [27]. Rivara et al [30] reported, in their preliminary histomorphological study, promising results at six-months follow-up, with the significant formation of new bone tissue (39.84% ± 2.96). Stievano et al [42] performed a retrospective survival study of dental implants positioned in regenerated bone after maxillary sinus augmentation with the Biogen mix, without histological or histomorphometric analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The histomorphometric analyses revealed a mean formation of the new bone of 23.5% [27]. Rivara et al [30] reported, in their preliminary histomorphological study, promising results at six-months follow-up, with the significant formation of new bone tissue (39.84% ± 2.96). Stievano et al [42] performed a retrospective survival study of dental implants positioned in regenerated bone after maxillary sinus augmentation with the Biogen mix, without histological or histomorphometric analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Sinus floor augmentation through a bone substitute is less invasive than autogenous bone and shows comparable results in terms of implant survival rates [11,21]. Today, a multitude of bone substitute materials with demonstrated acceptable outcomes in terms of biocompatibility and long-term stability are available from several specialized companies [22,23], and several investigations on anorganic bovine bone (ABB) [15,[24][25][26] and deproteinized equine bone mineral (DEBM) have been conducted [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Equine-derived bone substitutes have been described as having the ability to induce osteoblastic differentiation and angiogenesis while being absorbed by osteoclasts. In addition, the presence of neoplastic bone associated with remodeling effects was observed around the graft material 6 months postoperatively, while being described in cases of successful sinus lift [47], [48].…”
Section: Bone Grafting Physiologymentioning
confidence: 98%
“…Modern implant dentistry is tightly connected to bone augmentation procedures, especially when implant insertion follows a prosthetic planning concept. Among numerous bone grafting techniques, one of the most frequently used procedures is maxillary sinus floor augmentation [1]. Surgical techniques vary in the way the sinus cavity is accessed (lateral or crestal approach) and the type of grafting material placed into the cavity [2].…”
Section: Introductionmentioning
confidence: 99%